1993
DOI: 10.1577/1548-8667(1993)005<0036:hoglap>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Gill, Liver, and Pancreas, and Serum Enzyme Levels of Channel Catfish Infected withAeromonas hydrophilaComplex

Abstract: Channel catfish Ictalurus punctatus infected with Aeromonas hydrophila complex were examined 2-21 d after they were moved from earthen ponds to tanks. These infections by A. hydrophila complex were categorized into three groups: (1) motile aeromonad septicemia (MAS; systemic infection and signs of disease), (2) cutaneous (infection limited to skin and the underlying muscle), and (3) latent (systemic infection but no external signs of disease). Hepatic necrosis was associated with all types of infections but wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 15 publications
5
31
0
Order By: Relevance
“…In present study, pigments such as haemosiderin, lipofuscin, and hematoidine were not observed in the liver and spleen of any case. In the liver; detection of subcapsular, perivascular and peripacreatic lymphocyte infiltration was consistent with those in literature (1,7,9,13,24).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In present study, pigments such as haemosiderin, lipofuscin, and hematoidine were not observed in the liver and spleen of any case. In the liver; detection of subcapsular, perivascular and peripacreatic lymphocyte infiltration was consistent with those in literature (1,7,9,13,24).…”
Section: Discussionsupporting
confidence: 91%
“…Also Ventura & Grizzle (13) reported that fish with only cutaneous infections may have several types of concealed lesions including increased amounts of lipofuscin and haemosiderin in the liver and spleen; however most visceral organs were not necrotic. In present study, pigments such as haemosiderin, lipofuscin, and hematoidine were not observed in the liver and spleen of any case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the kidney of ulcer diseased farmed fishes. Diseased catfish, with external signs or having latent infection could be diagnosed through histopathological study of various organs like skin, muscle, gill, kidney and liver as practiced by many workers (Ventura and Grizzle, 1988;Grizzle and Kiryu, 1993;Ruksana, 1998). Histopathological technique is one of the most important procedures for disease diagnosis in fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, fish may exhibit epithelial hyperplasia in the foregut, leptomeningeal congestion in the brain, as well as a thrombosis and inflammation in the perisclerotic region and corneal epithelium of the eye (Fuentes and Perez, 1998). There may also be a severe branchitis, as indicated by leucocytic infiltration and dilation of the central venous sinus (Grizzle and Kiryu, 1993). Systemic infections are characterized by diffuse necrosis in several internal organs and the presence of melanin-containing macrophages in the blood (Ventura and Grizzle, 1988).…”
Section: Introductionmentioning
confidence: 99%